Stndarization Of The Recipe For Beef Randang As Traditional Food In Nagari Pakan Rabaa - Murfiqah Fadhilah; Elida Elida (Universitas Negeri Padang, 2020)
This research was conducted to obtain a good and correct standard of meat randang recipe. The method used is a combination method, namely a combination of qualitative and quantitative research. Using two sources, namely: qualitative data sources were obtained from people who were smart or knew they would be involved, while quantitative data were obtained from 5 expert panelists. The qualitative data collection technique uses three techniques, namely: data reduction, data presentation and conclusions, while the quantitative data collection technique uses the organoleptic test with the formula (Mx = (x / N). Based on the research conducted, the meat randang recipe, processing, used, the tools used and the expected quality of the meat randang. The recipe obtained is then converted and organoleptic tests are carried out to obtain the quality of the meat randang including: (shape, color, aroma, texture and taste)